Diverticulitis del ciego. Reporte de caso en un paciente joven - Julio Domínguez-Herrera; Pedro Vallejo-Casas; Giancarlo Sirtori-Campo; Ezio Pezzano-Molina; Jesús Iglesias-Acosta (Universidad del Norte, 2018)
Diverticulitis of the cecum is a rare cause of acute abdomen. We present the case of a 20-year-old female who was admitted with signs and symptoms consistent with acute appendicitis. However, cecal diverticulitis is evidenced intra-operatively and a right colectomy is performed followed by an ileocolic anastomosis. The patient recovered well and was discharged home on post-operative day five. This is the first known case in a patient of this age. Although rare, it is important to include cecal diverticulitis as a differential diagnosis in such scenarios as well as understand the many surgical techniques available for its management.